Theoretical determination of energies, wavelengths, and transition rates for the Y30+–Y36+ spectra of fusion interest. (November 2018) - Chen, Zhan-Bin; Wang, Kai; Guo, Xue-Ling
Highlights: Excitation energies, transition wavelengths, and transition probabilities for the L-shell charge states of yttrium ions are reported. Comparison with the recent EBIT spectra of the NIST allowed us to perform consistency checks and estimate the uncertainty of the data. The present data particularly important for fusion research. Abstract: We report a set of theoretical data for the energy levels, wavelengths, transition rates of electric/magnetic-dipole (E1/M1) and electric/magnetic-quadrupole (E2/M2) transitions for the L-shell charge states of Y 30 +, Y 31 +, Y 32 +, Y 33 +, Y 34 +, and Y 36 + and the similar spectroscopic data of the 166 fine-structure levels arising from the 2 s 2, 2 s 2 p, 2 p 2, 2 snl ( n =3, 4, 5; l =0, 1, 2, 3, 4), and 2 pnl ( n =3, 4, 5; l =0, 1, 2, 3, 4) configurations of Y 35 +, obtained using the second-order relativistic many-body perturbation theory (MBPT). The overall quality of the calculations is assessed by comparisons with the other available theoretical values and the measured spectra in the Electron Beam Ion Trap (EBIT) of the National Institute of Standards and Technology (NIST). For these yttrium ions, only a few levels have been experimentally established. The accuracy of our calculations is however high enough to facilitate identifications of observed lines. The present new data, fill in a gap in the available data of the extreme ultraviolet (EUV) transitions for these ions particularly important for fusion research where their spectra can provide diagnostic information on hot plasmas, in particular in fusion devices.